Kynurenine 3‐monooxygenase (KMO), and signal transducer and activator of transcription 3 (STAT3) expression is involved in tumour proliferation and predicts poor survival in canine melanoma. (4th September 2020) - Liu, I‐Li; Chung, Ting‐Fang; Huang, Wei‐Hsiang; Hsu, Chia‐Hui; Liu, Cheng‐Chi; Chiu, Yi‐Han; Huang, Kuo‐Chin; Liao, Albert Tai‐Ching; Lin, Chen‐Si
Abstract: Canine melanoma is a malignant tumour that exhibits aggressive behaviour, and frequently metastasizes to regional lymph nodes and distant sites. Currently, there are no effective treatments or practical prognostic biomarkers for canine melanoma. The enzyme kynurenine 3‐monooxygenase (KMO), which plays a central role in the tryptophan metabolism, has previously been identified as the main pathogenic factor in neurodegenerative diseases; however, it has recently been found to be positively associated with tumour malignancy in human hepatocellular carcinoma and canine mammary tumours. Signal transducer and activator of transcription 3 (STAT3) is a well‐known oncoprotein contributing to the proliferation, survival, invasiveness and metastasis of a variety of cancers. Although whether STAT3 and KMO collaborate in tumorigenesis needs to be further verified, our previous findings showed that inhibition of KMO activity reduced activation of STAT3. This study investigated the expressions of KMO and STAT3/phosphorylated (pSTAT3) by immunohistochemical analysis in 85 cases of canine melanoma, showing their expression levels were high within highly mitotic melanoma cells. KMO Overexpression was significantly associated with increased STAT3 and pSTAT3 expressions. Melanoma tissues with higher KMO, STAT3 and pSTAT3 protein expressions were correlated with reduced survival rates of the canine patients. Moreover, inhibition of KMO activity in canine melanoma cells resulted in reduced cell viability, in addition to decreased expressions of STAT3 and pSTAT3. Our results indicated the significance of KMO and the potential role of KMO/STAT3 interaction in enhancing tumour development. Additionally, KMO and STAT3/pSTAT3 may be viewed as useful biomarkers for the prediction of prognosis of canine melanoma.